Una nueva especie de Holmesina Simpson (Xenarthra, Cingulata, Pampatheriidae) del Pleistoceno de Rondônia, Sudoeste de la Amazonia, Brasil - Góis, Flávio (2012)
The Xenarthra Cingulata is one of the most characteristic groups in the Neotropical region. These American endemic mammals comprise several families, among them, the Pampatheriidae (middle Miocene-early Holocene) which are characterized by sharing traits with both the Dasypodidae and the Glyptodontidae. The genera Pampatherium Gervais & Ameghino and Holmesina Simpson, occur in both North and South America. In North America, the species H. floridanus, H. septentrionalis and P. mexicanum are recorded from the late Pliocene to the Pleistocene, whereas H. occidentalis, H. paulacoutoi, H. majus, P. humboldtii and P. typum are recorded in the Pleistocene of South America. New specie of the genus Holmesina is here proposed based on a skull without mandible found at the locality Araras/Periquitos, right margin of Madeira River, municipality of Vila Nova Mamoré, Rondônia State, from the Rio Madeira Formation (late Pleistocene-Holocene). The new specie differs from the other species of the genera Holmesina and Pampatherium by a series of distinctive morphological and allometric features: markedly slender skull, narrow straight nasals, slightly convex frontals, long parietals, and little developed sagittal crest. The zygomatic arch long and slender, without the large lateral area at orbital level observed in the other species, infraorbital process absent; temporal fossa wide and excavated/ deep; supraoccipital very high, deep, with external occipital crest prominent and lambdoid crest expanded posteriorly; palate narrow, with imbrication molariforms between MF2, MF3 and MF4.